Hand gesture controlled mobile robots and robotic arms - Aung Thura; Than Lin; Bohez, Erik L.J.; Somrak Petchartee (Pathum Thani : Asian Institute of Technology, 2016)
There are many ways to control a robot and one of the widely used ways is wireless control. Among the wireless control systems, hand gesture control is becoming a prevalent one in robotic field. Based on the movements of human hand, gesture based controlling process has several types using fingers, arm, wrist or detecting tilt of hands. The aim of this project is to develop a hand gesture based mobile robot and robotic arm. All parts in the robot are controlled by bending of fingers using flex sensors mounted on a hand glove. The robot has two parts: robotic arm and chassis with differential steering. Robot chassis has two wheels connected with DC motors and a caster wheel. A gripper and 1 DOF robotic arm are used for the robotic arm and two servo motors work for the robot arm system. For wireless communication, XBee series 2 is used as it is capable for a long range network and two Arduino Uno boards are used for the hand glove and robot. The idea of the project is to control a robot wirelessly and use it in places where humans cannot go and complete the tasks.
A capstone project submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Mechatronics Engineering, School of Engineering and Technology
Capstone Project (B.Sc.)-Asian Institute of Technology, 2016
Keywords: Robot hands -- Control; Mobile robots -- control